2018
DOI: 10.1371/journal.pone.0203950
|View full text |Cite
|
Sign up to set email alerts
|

“She must have been sleeping around”…: Contextual interpretations of cervical cancer and views regarding HPV vaccination for adolescents in selected communities in Ibadan, Nigeria

Abstract: BackgroundHuman Papilloma virus (HPV) vaccines for adolescents are pivotal in the control of cervical cancer, the commonest women specific malignancy in sub-Saharan Africa. Knowledge about cervical cancer have been reported to be low in Africa but expressed acceptability for HPV vaccines have been high. The reason for this mismatch is not clear. An understanding of the interpretation of cervical cancer and views about HPV vaccine are important as they can affect actual decision making regarding adolescents’ up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 36 publications
0
33
0
Order By: Relevance
“… 29 For example, most women in a qualitative study that was conducted in a community in Lagos, Nigeria, believed that cervical cancer is a direct effect of promiscuity. 30 However, these participants did not provide further information on the relationship between unprotected sex, sexually transmitted infection, and HPV infection and the risk of cervical cancer. 30 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 29 For example, most women in a qualitative study that was conducted in a community in Lagos, Nigeria, believed that cervical cancer is a direct effect of promiscuity. 30 However, these participants did not provide further information on the relationship between unprotected sex, sexually transmitted infection, and HPV infection and the risk of cervical cancer. 30 …”
Section: Discussionmentioning
confidence: 99%
“… 30 However, these participants did not provide further information on the relationship between unprotected sex, sexually transmitted infection, and HPV infection and the risk of cervical cancer. 30 …”
Section: Discussionmentioning
confidence: 99%
“…Although statistical significant difference is not observed, it can be inferred that a higher proportion seems to have problem with cervical screening, and it has been reported that knowledge about (and by implication, acceptance of) cervical cancer in Africa is lower than acceptability of HPV vaccines. 16 It has also been suggested that statements of evidence supporting effectiveness of cervical services could improve perceptions, especially as beliefs threaten existing programs; hence the need for context-specific evidence-based strategies advocated. [16][17][18] What this report contributes is an empirical data from Delta State, Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…16 It has also been suggested that statements of evidence supporting effectiveness of cervical services could improve perceptions, especially as beliefs threaten existing programs; hence the need for context-specific evidence-based strategies advocated. [16][17][18] What this report contributes is an empirical data from Delta State, Nigeria. The implication is in the need to advance the knowledge of cervical screening procedure.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 This underscores the relevance of ensuring HPV vaccination of young women in Nigerian communities. 6 The acceptability of the vaccines is defined as the willingness of an individual to be vaccinated. This is a factor that contributes to its uptake.…”
Section: Introductionmentioning
confidence: 99%